Explorations in Music and Esotericism - George, Leonard, 1957-; Roth, Marjorie, 1958- (Book collections on Project MUSE., 2023)
"Scholars explore from many fresh angles the interweavings of two of the richest strands of human culture-music and esotericism-with examples from the medieval period to the modern age. Music and esotericism are two responses to the intuition that the world holds hidden order, beauty, and power. Those who compose, perform, and listen to music have often noted that music can be a bridge between sensory and transcendent realms. Such renowned writers as Boethius expanded the definition of music to encompass not only sounded music but also the harmonic fabric of human and cosmic life. Those who engage in pursuits called "esoteric," from ancient astrology, magic, and alchemy to recent and more novel forms of spirituality, have also remarked on the relevance of music to their quests. Esotericists have composed music in order to convey esoteric meaning, performed music to create esoteric influences, and listened to music to raise their esoteric awareness. The academic study of esotericism is a young field, and few researchers have probed the rich interface between the musical and esoteric domains. In Explorations in Music and Esotericism, scholars from numerous fields introduce the history of esotericism and current debates about its definition and extent. The book's sixteen chapters present rich instances of connections between music and esotericism, organized with reference to four aspects of esotericism: as a form of thought; as the keeping and revealing of secrets; as an identity; and as a signifier. Edited by Marjorie Roth and Leonard George. Contributors: Elizabeth Abbate, Malachai Komanoff Bandy, Adam Bregman, Charles E. Brewer, Benjamin Dobbs, Anna Gawboy, Pasquale Giaquinto, Adam Knight Gilbert, Joscelyn Godwin, Virginia Christy Lamothe, Andrew Owen, Christopher Scheer, Codee Ann Spinner, Woodrow Steinken, and Daphne Tan"--